The revolving door indicator: Estimating the distortionary power of the revolving door - Elise S. Brezis; Joel Cariolle (Bar-Ilan University, Department of Economics, 2014)
The "revolving door" phenomenon has become very common in most industrialised countries, and is leading to conflicts of interest as well as economic distortions. The purpose of this paper is to develop an indicator of the distortionary effects of the revolving door - The Revolving Door Indicator (RDI). By measuring the sectorial concentration of the revolving door, this indicator intends to proxy the distortions induced by rent-seeking firms. The RDI is a first step to size up the distortive power of the revolving door.
Keywords: D7; K2; K4; L1; L2; L5; 330; revolving door; corruption; conflict of interest; regulations; distortions